Should It Stay or Should It Go? A Critical Reflection on the Critical Period for Language - Sergio Balari; Guillermo Lorenzo (Biolinguistics, 2015)
This paper tries to shed light on traditional and current observations that give support to the idea that language is subject to critical period effects. It is suggested that this idea is not adequately grounded on a view on language as a developmental phenomenon which motivates the suggestion of moving from the now classic concept of language as a ‘faculty’ to a new concept of language as a ‘gradient’: i.e. an aggregate of cognitive abilities, the weight of which is variable from one to another developmental stage, and which exercise crucial scaffolding effects on each other. Once this well-supported view is assumed, the idea of ‘critical period’ becomes an avoidable one, for language can instantiate different forms of gradation, none of which is inherently normal or deviant relatively to each other. In any event, a notion of ‘criticality’ is retained within this view, yet simply to name the transitional effects of scaffolding influences within the gradient.